Magnetic Resonance Imaging in a Patient with a Dual Chamber Pacemaker - Lynne Martina Millar; Andrew George Robinson; Maurice Thomas O'Flaherty; Niall Eames; Nicola Johnston; Gary Heyburn (Case Reports in Medicine)
Having a pacemaker has been seen an absolute contraindication to having an MRI scan. This has become increasingly difficult in clinical practice as insertion of pacemakers and implantable cardiac defibrillators is at an all time high. Here we outline a case where a 71-year-old male patient with a permanent pacemaker needed to have an MRI scan to ascertain the aetiology of his condition and help guide further management. Given this clinical dilemma, an emergency clinical ethics consultation was arranged. As a result the patient underwent an MRI scan safely under controlled conditions with a consultant cardiologist and radiologist present. The results of the MRI scan were then able to tailor further treatment. This case highlights that in certain conditions an MRI can be performed in patients with permanent pacemakers and outlines the role of clinical ethics committees in complex medical decision making.